A multi-objective path planning method for the wave glider in the complex marine environment. (15th November 2022) - Zhang, Shuai; Sang, Hongqiang; Sun, Xiujun; Liu, Fen; Zhou, Ying; Yu, Peiyuan
Abstract: Aiming to energy-efficient, short path, and safety, an online dynamic multi-objective path planning method for the wave glider (WG) is proposed to make the WG operate efficiently in the uncertain marine environment. In this paper, a novel kinematic constrained safe rapidly-exploring random tree (KS-RRT*) path planning algorithm is developed, which is subject to the safe area boundaries and kinematics. Biased random sampling method is introduced which the kinematic constraints is used as heuristic function and the KS-RRT* can reduce the extended area of random points. And a path safe (PS) scheme is developed, which can ensure that the WG safely passes through the planned path. In addition, energy cost, path length, and safety metric (SM) of each feasible trajectory are obtained by the KS-RRT*, the technique for order preference by similarity to ideal situation (TOPSIS) is utilized to solve multi-objective path optimization problem, and the final path is smoothed by the B-spline algorithm. The results of simulations show that the proposed KS-RRT* is more suitable for the WG's path planning than traditional path planning algorithm and the proposed multi-objective path optimization method can solve the path planning problem of the WG in complex marine environments. Highlights: Multi-objective path planning for energy savings, short paths, and safety. KS-RRT* path planning algorithm is subjected to the safe area and kinematics. Path safe scheme for make the wave glider safely passes through the planned path. TOPSIS and B-spline are used to solve multi-objective path optimization problem.